Watson-Crick Petri net languages with finite sets of final markings - Mohamad Jan, Nurhidaya; Fong, Wan Heng; Sarmin, Nor Haniza; Turaev, Sherzod (AIP Publishing, 2014)
A Watson-Crick Petri net is a new formal model that enhances a Petri net with the Watson-Crick complementary feature adapted from DNA molecules. The transitions of a Watson-Crick Petri net are labeled with pairs of symbols, and a firing sequence of transitions of the Watson-Crick Petri net is considered as successful if and only if it produces complete double stranded sequences of symmetrically related symbols according to some mode of execution termination of the firing of transitions. As an execution termination mode, we can consider the set of all reachable markings and a finite set of final markings. In this research, we investigate the fundamental properties of Watson-Crick Petri net languages with finite sets of final markings.